2008
DOI: 10.1159/000128560
|View full text |Cite
|
Sign up to set email alerts
|

Unrestored Dentin Caries and Deep Dentin Restorations in Swedish Adolescents

Abstract: The objectives of this longitudinal study were to assess: (a) the prevalence of unrestored dentin caries among 15-year-olds, (b) the proportion of these lesions that had progressed to deep dentin lesions (inner half of dentin) since the immediately preceding examination at the age of 14 and (c) the frequency of deep restorations (extending into the inner half of the dentin). The sample consisted of all 15-year-olds (n = 2,487) born in 1990 and included in the Public Dental Service in Malmö, Sweden. Bitewing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
2
27
2
1
Order By: Relevance
“…h The probability of an enamel lesion progressing within a 6-monthly cycle was calculated based on 2 studies (Flório et al 2001;Liu et al 2012). Similar data for dentinal lesions were calculated from a Swedish cohort study of 14-y-olds (Ridell et al 2008). …”
Section: Validity Parameters and Transition Probabilitiesmentioning
confidence: 99%
“…h The probability of an enamel lesion progressing within a 6-monthly cycle was calculated based on 2 studies (Flório et al 2001;Liu et al 2012). Similar data for dentinal lesions were calculated from a Swedish cohort study of 14-y-olds (Ridell et al 2008). …”
Section: Validity Parameters and Transition Probabilitiesmentioning
confidence: 99%
“…In a Swedish study the prevalence of lesions in approximal surfaces increased from 39% at the age of 12 to 72% at the age 20-21 [Mejàre et al, 1998]. Additionally, longitudinal studies have demonstrated that the overall caries incidence was considerably lower in young adults than in adolescents [Mejàre et al, 2004;Ridell et al, 2008]. However, a Danish study of teenagers demonstrated that the caries incidence in permanent molars rose slightly with age [Parner et al, 2007].…”
Section: Discussionmentioning
confidence: 97%
“…Cross-sectional studies have shown that younger adults have more caries lesions than older adults [Dummer et al, 1988;Bjarnason et al, 1997;Ridell et al, 2008;Demirci et al, 2010]. In a Swedish study the prevalence of lesions in approximal surfaces increased from 39% at the age of 12 to 72% at the age 20-21 [Mejàre et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations